(untitled) (Research, Society and Development, 2022)
Microalgae species such as Scenedesmus sp. have a high potential for lipid accumulation in their cells, enabling studies aimed at the exploration of these organisms as raw materials for the bio-oil extraction for biodiesel production, enhancing the biomass cultivation and harvesting systems. This study was developed to evaluate cultivation techniques of the Scenedesmus sp. microalgae that allows greater production of bio-oil. Cultivation took place in horizontal flat acrylic reactors, maintained at room temperature at 25 °C ± 1 °C, with a photoperiod controller in 12 hours of light and 12 hours of darkness, using three 40-volt white fluorescent lamps. The culture medium, time, and percentage of inoculum were the variables optimized for algae growth and lipid yield. To minimize the number of experiments and time, 23 factorial and central composite designs were used. The analyzes indicated that the cultivation of Scenedesmus sp. microalgae presented better yields in the lipid content when submitted to the cultivation in Chu medium with 20% of the initial inoculum. However, the lipid accumulation reaches a maximum when the initial concentration of Chu medium is approximately 39.5%. It was also found that the number of days (time) indicated the tendency of greater lipid accumulation in 20 days of cultivation. For these conditions of initial concentration of Chu medium (39.5%) and cultivation time (20 days), the model predicts an accumulation of lipid content of approximately 9.74%.